Pembrolizumab in combination with tocilizumab in high-risk hospitalized patients with COVID-19 (COPERNICO): A randomized proof-of-concept phase II study. (October 2022) - Sánchez-Conde, Matilde; Vizcarra, Pilar; Pérez-García, José Manuel; Gion, María; Martialay, María Pilar; Taboada, Javier; Alonso-Fernández, Alberto; Sampayo-Cordero, Miguel; Malfettone, Andrea; Tena, Isabel; Torre, Sergio De La; Llombart-Cussac, Antonio; et al.
Highlights: The optimal management of severe COVID-19 represents an unmet clinical need. Programmed cell death-1/interleukin-6 receptor blockade might restore immunocompetence and interrupt hyperinflammation. COPERNICO assessed pembrolizumab plus tocilizumab and standard of care (SOC) compared with SOC in high-risk patients with COVID-19. The addition of pembrolizumab plus tocilizumab to SOC reduced the hospitalization period. The addition of pembrolizumab plus tocilizumab to SOC reduced the rate of discharge without sequelae. Abstract: Objectives: Severe COVID-19 is associated with immune dysregulation and hyperinflammation (lymphocyte exhaustion and elevated interleukin 6. Pembrolizumab (P; immune-activating anti-programmed cell death-1 antibody) plus tocilizumab (TCZ; anti- interleukin 6 receptor antibody) might interrupt the hyperinflammation and restore cellular immunocompetence. We assessed the efficacy and safety of P + TCZ + standard of care (SOC) in high-risk, hospitalized patients with COVID-19 pneumonia without mechanical ventilation. Methods: Randomized, controlled, open-label, phase II trial in patients with severe SARS-CoV-2 infection to assess the hospitalization period to discharge. Results: A total of 12 patients were randomized (P + TCZ + SOC, n = 7; SOC, n = 5). Nine (75%) were males, with a median age of 68 (41-79) years. The median time to discharge for P + TCZ + SOC and SOC was 10 and 47.5 days ( P = 0.03), with zero (n = 1 patient had P-related grade 5 myositis) and two COVID-19-related deaths, respectively. Conclusion: The addition of P and TCZ to SOC reduced the hospitalization period, with higher and faster discharges without sequelae than SOC alone.